Electrospinning for high performance sensors - Macagnano, Antonella; Zampetti, Emiliano; Kny, Erich (NanoScience and Technology,, 2015)
This book aims to present the different aspects of electrospinning for designing and fabricating high performing materials for sensors applied in gaseous and liquid environments. Since electrospinning is a versatile and inexpensive manufacturing technology, the book emphasizes the industrial applications perspective. The volume is an edited collection of the most recent and encouraging results concerning advanced nanostructured (bio)sensors. The feats achieved by these sensors range from high sensitivity to extreme operating conditions and satisfy a wide range of requirements. Most of the contributions in this book come from First International Workshop on Electrospinning for High Performance Sensing (EHPS2014) that was held in Rome in 2014, as part of the European COST Action MP1206 Electrospun Nano-fibres for bio inspired composite materials and innovative industrial applications.